2018
DOI: 10.14419/ijet.v7i3.12.15906
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Treated Natural Jute Fiber on Flexural Properties of Reinforced Concrete Beams

Abstract: India is one of the largest producers of jute, its potential use in many branches of engineering should be developed for the prosperity of the nation. The recent trends in utilizing the natural fibers has increased due to its advantages over synthetic fibers due to low cost, low environment hazard and easy availability. The properties of the fiber is improved by treating the jute fiber with alkali and latex polymer. Since, very few studies been conducted using the treated jute fiber concrete, an experimental w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Table 7 shows the compressive strengths that were obtained from the tests performed on the cylinder specimens and the flexural strength of the beams subjected to bending after the 28-day curing time. In general, research indicates that concrete composite beams that incorporate natural fibres exhibit superior flexural strength and deflection resistance when compared to conventional concrete beams [32,33].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Table 7 shows the compressive strengths that were obtained from the tests performed on the cylinder specimens and the flexural strength of the beams subjected to bending after the 28-day curing time. In general, research indicates that concrete composite beams that incorporate natural fibres exhibit superior flexural strength and deflection resistance when compared to conventional concrete beams [32,33].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…De Azevedo et al [29] suggested that natural fibers exhibited promising potential in augmenting the flexural strength of geopolymer matrices. Several researchers [30][31][32][33][34][35][36] highlighted the ability of natural fibers in improving the structural behavior of RC beams. Others [37,38] used natural fibers in the renovation of RC columns.…”
Section: Introductionmentioning
confidence: 99%